Geochemical patterns of the Akdagmadeni (Yozgat, Central Turkey) fluorite deposits and implications - Şaşmaz, Ahmet; Yavuz, Fuat; Sağıroğlu, Ahmet; Akgül, Bünyamin (My University, 2005)
Fluorite and fluorite-bearing Pb–Zn–Ag (Cu) deposits are quite common in granitoids and associated skarn formations that are products of Late Cretaceous–Early Paleocene magmatic intrusions into Paleozoic metamorphic rocks of the so called Central Anatolian massif. This study investigates the geochemical features, mainly REE distributions, of fluorites from the Akdagmadeni fluorite and fluorite bearing Pb–Zn–Ag (Cu) deposits. These include the vein type Tad Dere, epidote-skarn hosted Bu¨yu¨kc¸al Tepe and the skarn and granite hosted Akc¸akisla deposits. The REE contents of these deposits are 20.6–48.5 ?x ¼ 36:0?, 61.3–149.3 ?x ¼ 113:0? and 279.2–4222.4 ?x ¼ 1280:0? ppm for the Tad D., Bu¨yu¨kc¸al T. and Akc¸akisla, respectively. In general, theREE contents are intermediate to high and decrease in abundance with increasing distance from the granitic bodies. The LREE contents are dominantly higher than HREE contents and REE normalized patterns indicate decreasing abundances with increasing atomic number. These indicate that all the fluorites are early stage mineralizations. However, Tb/Ca–Tb/La ratios show distinct differences in the nature of the mineralizing fluids. The high ratios of Akc¸akisla fluorites are evidence of mineralizing fluids rich in late-stage differentiates from a felsic magma, while intermediate to high ratios of the Bu¨yu¨kc¸al T. fluorites are products of late-stage differentiates from hydrothermal fluids. Tad D. fluorites were mineralized under hydrothermal conditions. Decreasing SREE contents in the order of Akc¸akisla, Bu¨yu¨kc¸al T., and Tad D., and Sc/Eu vs Sr distribution (Sr increases with increasing distance from the magmatic rocks) also supports this order of formation. Each of the three types of fluorite deposits plot in well-defined areas in the Sc/Eu vs Sr diagram. Eu and Ce anomalies give a mixed pattern; the Tad D. fluorites have strong negative Eu anomalies indicating low T and low f o2 mineralizing fluids. Strong positive Eu anomalies for the Akc¸akisla fluorites are probably due to high f o2: The Ce anomalies are strongly negative for the Akc¸akisla, negative for the Bu¨yu¨kc¸al T. and weakly negative for the Tad D. fluorites. These indicate high f o2 conditions for the Akc¸akisla, intermediate for the Bu¨yu¨kc¸al T. and low for the Tad D. fluorites. Because of distinguishable differences in REE patterns, the fluorite deposits plot in well-defined areas in Sc/Eu vs Sr, (La/Yb)n– (Eu/Eup)n, Sr–(Eu/Eup)n, Sc–SREE, (Tb/Yb)n–(La/Yb)n, Tb/Ca–Tb/La diagrams, and indicate different origins and depositional histories. The homogenization temperatures ?TH? range from 156 to 185 8C with the corresponding salinities between 12 and 23 wt% NaCl for the Tad Dere ores, 390 to 430 8C with the corresponding salinities 8 and 12 wt% NaCl for the Akc¸akisla and Bu¨yu¨kc¸al Tere ores. Consequently, the field, fluid inclusion data and REE geochemistry indicate that the composition of mineralizing fluids, the locations of ore formations relative to the plutons, the mineralizing mechanisms and the prevailing physicochemical conditions of the depositional environments for the fluorite deposits of Akdagmadeni, were different.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Fluorite; REE; Precious metals; Trace elements; Akdagmadeni